2003
DOI: 10.1002/bjs.4040
|View full text |Cite
|
Sign up to set email alerts
|

Lesion progression with time and the effect of vascular occlusion following radiofrequency ablation of the liver

Abstract: The efficacy of RFA in liver increases with occlusion of the portal vein or hepatic artery. The extent of secondary heat-induced necrosis in liver parenchyma should be considered for determination of the final size of the ablated area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 23 publications
2
48
1
5
Order By: Relevance
“…Several studies have demonstrated tumor necrosis following hyperthermia. 25,26 For example, Nikfarjam et al 26 reported cell death and vascular injury after laser-induced hyperthermia treatment to the liver and colorectal metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated tumor necrosis following hyperthermia. 25,26 For example, Nikfarjam et al 26 reported cell death and vascular injury after laser-induced hyperthermia treatment to the liver and colorectal metastases.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by Goldberg et al (23), who reported the role of the adjuvant effect of chemotherapy on RF ablation in a subcutaneous tumor model and noted that at least 48 hours were required before coagulation fully evolved. The development and evolution of thermally ablated tissue over time at hematoxylin-eosin staining has been explored by others (24,25). It is agreed that a clear appearance of cell damage in the ablated area does not manifest on hematoxylin-eosinstained images within 1 or 2 days after thermal ablation.…”
Section: Experimental Studies: Contrast-enhanced Us For Monitoring Anmentioning
confidence: 99%
“…Die größte Serie neuroendokriner Lebermetastasen wurde von Seifert et al [7] berichtet, der 13 Patienten mit 52 Leberherden therapierte. In dieser Serie konnte bei 5 von 7 symptomatischen Patienten eine Symptomfreiheit erreicht werden.…”
Section: Kryoablationunclassified
“…1 und 2). Ein wesentlicher Vorteil des offenen Zugangswegs ist die Möglichkeit, die Leberperfusion temporär mittels Pringle-Manöver zu unterbrechen; hierdurch wird die Größe der Ablationsnekrose erhöht und die Variabilität deutlich verringert [12,13]. In den oben genannten Übersichtsarbeiten wurden jeweils über 5000 publizierte Ablationen mit Angaben zum Follow-up für einen Zeitraum von mindestens 6 Monaten ausgewertet.…”
Section: Stippelunclassified